2021
DOI: 10.1177/26338076211065208
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of both legal and nonlegal factors on following a vehicle too closely utilizing three deterrence-based theories

Abstract: Following a vehicle too closely (otherwise known as tailgating) is a high-risk behavior and major contributor to motor-vehicle collisions and injuries. Both legal and nonlegal countermeasures are currently in place in an attempt to prevent this behavior, yet there has been limited research that has examined the effectiveness of both legal and nonlegal factors on engagement in the behavior. Therefore, this research utilized a combination of the three most salient deterrence-based theories used in road safety to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Consistent with previous research, perceived swiftness of punishment failed to deter drivers in the case of drug driving (Davey et al, 2008), drink driving (Szogi et al, 2017), and speeding (Truelove et al, 2017). In addition, the extended timeframe between getting caught and appearing in court for drink driving and drug driving could delay the consequences of illegal behavior and thus, weaken the swiftness effect (Nagin & Pogarsky, 2001). Similarly, speeding and being detected by a speed camera takes time until the offender receives the fine or feels its financial effects.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous research, perceived swiftness of punishment failed to deter drivers in the case of drug driving (Davey et al, 2008), drink driving (Szogi et al, 2017), and speeding (Truelove et al, 2017). In addition, the extended timeframe between getting caught and appearing in court for drink driving and drug driving could delay the consequences of illegal behavior and thus, weaken the swiftness effect (Nagin & Pogarsky, 2001). Similarly, speeding and being detected by a speed camera takes time until the offender receives the fine or feels its financial effects.…”
Section: Discussionsupporting
confidence: 81%
“…The lack of longitudinal data deprived us form addressing the temporal ordering of variables in terms of the offending driving behaviors and the outcome of sanctioning experiences and how the formulation of perceptions changes over time. However, previous research investigated deterrence in the road safety domain measured offending behavior on a scale ranging from “never” to “all the time” (Ochenasek et al, 2022; Szogi et al, 2017; Truelove et al, 2017). Despite this, we acknowledge that the cross-sectional data used in this study neglected the number of prior experiences, the nature, the timing and the recency of past behaviors.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Overall, this study identifies the large prevalence of these applications that display traffic enforcement locations and the wide range of ways in which they have the potential to be used to avoid being caught and punished for committing a traffic offense. This is alarming if the applications enable more people to avoid being caught and punished for traffic violations, since punishment avoidance has consistently been demonstrated to be one of the most salient predictors of continued engagement in offending behaviors (Fleiter & Barry, 2005;Ochenasek et al, 2021;Szogi et al, 2017;Truelove et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the use of the applications may instead decrease perceptions of apprehension certainty by increasing perceptions that they can avoid being detected and subsequently punished for the offense (Stafford & Warr, 1993). Previous road safety literature has demonstrated that punishment avoidance is a leading predictor of continued engagement in offending behavior (e.g., Fleiter & Barry, 2005;Ochenasek et al, 2021;Szogi et al, 2017;Truelove et al, 2019). The way in which drivers may avoid being caught for a traffic offense can depend on whether they are violating a transient or fixed rule.…”
Section: Introductionmentioning
confidence: 99%